The fatty acid composition and properties of oil extracted from cotton (Gossypium herbaceum) seed of Bangladesh - Roy, SK; Karim, SMM; Rahman, Z; Aziz, S; Hassan, SMM (Bangladesh Journal of Scientific and Industrial Research, 2012)
Gossypium herbaceum (cotton) seed oil was investigated to determine the fatty acid composition and proximate analyses. The seed contains 15.0% of fatty oil. The saturated and unsaturated fatty acid each comprises 21.73% and 78.27%, respectively, of the oil. The percent composition of the extracted oil was identified by gas liquid chromatography. Among the identified fatty acid oleic acid contributed to the highest proportion (29.40)%, where as palmitic acid, stearic acid, linoleic acid and ecosenoic acid combinedly contributed to the rest 70.60%. Proximate analysis showed that Gossypium herbaceum seed could be considered as a good source of oleic acid as well as it can be treated as edible oil (after refining). By removing gossypol, a toxic yellow polyphenolic compound produced by cotton and other members of the order Malvaceae, it can be considered as an edible oil. Activated charcoal can be used in this purpose. DOI: http://dx.doi.org/10.3329/bjsir.v47i3.13064 Bangladesh J. Sci. Ind. Res. 47(3), 303-308 2012